84.1k views
1 vote
Help 15 points

Find the product. (6g – 5h)2

(a) 36g2 – 25gh + 25h2

(b) 36g2 – 60gh + 25h2

(c) 36g2 – 60gh – 25h2

(d) 36g2 + 25h2

2 Answers

3 votes

Answer:

36 g^2 + -60 g h + 25 h^2 thus: B

Explanation:

Expand the following:

(6 g - 5 h)^2

(6 g - 5 h) (6 g - 5 h) = (6 g) (6 g) + (6 g) (-5 h) + (-5 h) (6 g) + (-5 h) (-5 h):

6×6 g g - 5×6 g h - 5×6 h g - 5 (-5) h h

6 g×6 g = 6×6 g^2:

6×6 g^2 - 5×6 g h - 5×6 h g - 5 (-5) h h

6×6 = 36:

36 g^2 - 5×6 g h - 5×6 h g - 5 (-5) h h

6 (-5) = -30:

36 g^2 + -30 g h - 5×6 h g - 5 (-5) h h

-5×6 = -30:

36 g^2 - 30 g h + -30 h g - 5 (-5) h h

-5 h (-5) h = -5 (-5) h^2:

36 g^2 - 30 g h - 30 h g + -5 (-5) h^2

-5 (-5) = 25:

36 g^2 - 30 g h - 30 h g + 25 h^2

g h (-30) + h g (-30) = -60 g h:

Answer: 36 g^2 + -60 g h + 25 h^2

User Dawan
by
5.1k points
6 votes

Answer:(b). 36g2-60gh+25h2

Explanation:

(6g-5h)2

=(6g-5h)(6g-5h)

=36g2-30gh-30gh+25h2

=36g2-60gh+25h2

User Nirvana
by
5.4k points